PENGEMBANGAN MANAJEMEN PENYIARAN WALISONGO TV - Hendro W, Nur Cahyo (Islamic Communication Journal, 2017)
Television is the media most widely consumed by the people of the world and especially Indonesia, with conditions like this the influence of television to be very large on the mindset and patterns of public attitudes. Faculty of Dawah and Communications UIN Walisongo as an institution that is responsible for the success of Islamic propagation in Indonesia is very appropriate to use television as one of his dawah media. The management of broadcast television is classified into modern management because all activities in preparing and producing broadcast can not be separated from computer technology. computers have an enormous influence in speeding up a product, with collaboration between software will create new innovation results in broadcast television. The programs that will be presented must be well managed, by conducting scheduling time management of the expected broadcast programs that will be served can be anticipated as early as possible. The production process of television broadcasting must be done before the program is aired. Through the process of film editing in which there is a payload of information a television program can be produced. TV broadcasting program is integrated with Walisongo TV broadcast management information system software.————————————————————————————Televisi adalah media yang paling luas dikonsumsi oleh masyarakat dunia dan khususnya Indonesia, dengan kondisi seperti ini pengaruh televisi menjadi sangat besar terhadap pola pikir maupun pola sikap masyarakat. Fakultas Dakwah dan Komunikasi UIN Walisongo sebagai sebuah institusi yang ikut bertanggung jawab atas berhasilnya dakwah Islam di Indonesia sangatlah tepat untuk menggunakan televisi sebagai salah satu media dakwahnya. Managemen siaran televisi digolongkan kedalam manajemen modern karena semua aktivitas dalam mempersiapkan dan memproduksi siaran tidak bisa lepas dari teknologi komputer. komputer mempunyai pengaruh yang sangat besar dalam mempercepat menghasilkan sebuah produk, dengan kolaborasi antar software akan tercipta hasil inovasi baru dalam siaran televisi. Program-program yang akan disajikan harus dikelola dengan baik, dengan melakukan managemen penjadwalan waktu siaran diharapkan program-program yang akan ditayangkan dapat diantisipasi sedini mungkin. Proses produksi siaran televisi harus dikerjakan sebelum program tersebut ditayangkan. Melalui proses editing film yang didalamnya terdapat muatan informasi sebuah program tayangan televisi dapat dihasilkan. Program siaran televisi tersebut diintegrasikan dengan software sistem informasi manajemen siaran Walisongo TV.